2018
DOI: 10.1259/bjr.20180262
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating spinal intradural-extramedullary schwannoma from meningioma using MRI T  2 weighted images

Abstract: Signal intensity ratio of the spinal tumor and fat on T weighted images is useful for differentiating schwannomas from meningiomas to obtain an accurate diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 26 publications
1
22
0
1
Order By: Relevance
“…[4,5] Although both tumors are mostly benign, there is a substantial difference between the surgical techniques for removing each. [6,7] Since spinal meningiomas have a tendency to recur, complete tumor resection with dural excision is recommended whenever practicable to lower the recurrence rate. [6,8,9] Thus, radiologic differentiation between these two spinal tumors is a crucial step in surgical planning.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4,5] Although both tumors are mostly benign, there is a substantial difference between the surgical techniques for removing each. [6,7] Since spinal meningiomas have a tendency to recur, complete tumor resection with dural excision is recommended whenever practicable to lower the recurrence rate. [6,8,9] Thus, radiologic differentiation between these two spinal tumors is a crucial step in surgical planning.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Many studies have reported MRI to be useful in differentiating between intradural extramedullary schwannomas and meningiomas. [1,7,13,14] Besides locating the tumor, dural tail sign or neural foraminal extension was suggested as a useful imaging feature in differentiating between the two histologic subtypes. [4,7,13,14] Signal intensity of the tumor on T2-weighted image was also shown to be helpful for the differentiation; schwannomas have a tendency to show a hyperintense signal while a substantial portion of meningiomas shows an isointense signal compared to that of the spinal cord.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mm contributes to two‐thirds of lumbar segmental stability and is said to play an important role in trunk function. We divided the fatty degeneration of the lumbar portion of the Mm into intramyocellular lipids (IMCL) and extramyocellular lipids (EMCL) components using MRS and found that IMCL was associated with chronic LBP …”
Section: Ivd and Advances In Diagnostic Imagingmentioning
confidence: 99%
“…We divided the fatty degeneration of the lumbar portion of the Mm into intramyocellular lipids (IMCL) and extramyocellular lipids (EMCL) components using MRS and found that IMCL was associated with chronic LBP. [25][26][27]…”
Section: Relationship Between the MM Fatty Degeneration And Lbpmentioning
confidence: 99%